2021
DOI: 10.3390/en15010143
|View full text |Cite
|
Sign up to set email alerts
|

Thermophoresis and Brownian Effect for Chemically Reacting Magneto-Hydrodynamic Nanofluid Flow across an Exponentially Stretching Sheet

Abstract: This comparative research investigates the influence of a flexible magnetic flux and a chemical change on the freely fluid motion of a (MHD) magneto hydrodynamic boundary layer incompressible nanofluid across an exponentially expanding sheet. Water and ethanol are used for this analysis. The temperature transmission improvement of fluids is described using the Buongiorno model, which includes Brownian movement and thermophoretic distribution. The nonlinear partial differential equalities governing the boundary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 39 publications
(39 reference statements)
0
13
0
Order By: Relevance
“…Sheriff et al [ 37 ] investigated varying fluid features for water-based nanoparticles for heat and peristaltic propagation. Numerous researchers have utilized nanofluids and hybrid nanofluids to enhance the heat transfer coefficient, including several quality studies [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sheriff et al [ 37 ] investigated varying fluid features for water-based nanoparticles for heat and peristaltic propagation. Numerous researchers have utilized nanofluids and hybrid nanofluids to enhance the heat transfer coefficient, including several quality studies [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nandeppanavar et al [ 5 ] performed a theoretical analysis of Casson nanofluid flow over an exponentially stretching surface for thermal transmission. Arshad et al [ 6 ] discussed the MHD nanofluid movement across an exponentially stretching surface using the Brownian effect. Hussain et al [ 7 ] have explored three-dimensional rotating nanofluid over a stretching surface with a magnetic field for heat transportation.…”
Section: Introductionmentioning
confidence: 99%
“…Gowda et al [14] have demonstrated Casson-Maxwell fluid through stretchable disks to examine slip flow [15][16][17][18][19]. and Arshad et al [20][21][22] have extensively examined linear and exponential stretching surfaces with external applied effects for nano and hybrid nanofluids.…”
Section: Introductionmentioning
confidence: 99%